Establishing Drug Effects on Electrocorticographic Activity in a Genetic Absence Epilepsy Model: Advances and Pitfalls - van Luijtelaar, Gilles; van Oijen, Gerard (Frontiers in Pharmacology, 2020)
The genetic rat models such as rats of the WAG/Rij strain and GAERS were developed as models for generalized genetic epilepsy and in particular for childhood absence epilepsy. These animal models were described in the eighties of the previous century and both models have, among others, face, construct and predictive validity. Both models were and are currently used as models to predict the action of antiepileptic medication and other experimental treatments, to elucidate neurobiological mechanisms of spike-wave discharges and epileptogenesis. The EEG is imperative for establishing absence seizures and to quantify them. Here an overview is given regarding the design of EEG drug evaluation studies, which animals to use, the dependent variables, the necessity to observe and quantify the behavior of the rats as well, some pitfalls regarding the interpretation of the data, and some developments in EEG technology.